User Acceptance of Electronic Medical Records Implementation at Kijang Community Health Center Using the Technology Acceptance Model - Kusumo, Retno; Pradita, Riska (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Currently, all Primary Health Facilities (FKTP) are required to implement electronic medical records. Their use can improve efficiency in patient data management, ease access to medical information, and enable real-time data sharing. Analyzing user acceptance is necessary for the transition to electronic medical records. Some users are unfamiliar with how to operate electronic medical records due to a lack of socialization, and unrestricted user access rights are also a barrier. The lack of standard operating procedures (SOPs) for electronic medical records implementation also contributes to inadequate implementation. The purpose of this study was to analyze user acceptance of the implementation of electronic medical records using the Technology Acceptance Model (TAM) based on perceived ease of use, perceived usefulness, attitude toward use, behavioral intention to use, and actual use. This study was a quantitative descriptive study with a cross-sectional design. The study location was Kijang Community Health Center, with electronic medical record users as the subjects. Data collection was conducted through questionnaires, with questionnaires serving as the research instrument. The results of the analysis of user acceptance of electronic medical records using the TAM method on the aspect of perceived ease of use of 87.5%, on the aspect of perceived usefulness of 80.5%, on the aspect of attitude toward using of 86.1%, on the aspect of behavioral intention to use of 84.7%, and related to the aspect of actual use of 85.1%. Conclusion: user acceptance of the implementation of electronic medical records at the Kijang Health Center based on the TAM method is that electronic medical records are considered easy to use, and provide benefits in carrying out work by users. In addition, it is considered to provide comfort when doing work, users also want to continue using it, and its implementation is in accordance with the modules and guidelines.